Rural residents' willingness to participate in basic medical insurance and influential factors: A survey of three provinces in China - Tian, Guomei; Xu, Jinpeng; Zhang, Ting; Zhang, Hongyu; Liu, Jian; Shi, Qi; Deng, Fangmin; Chen, Fangting; He, Jingran; Wu, Qunhong; Kang, Zheng; Wang, Hui (Frontiers in Public Health, 2022)
Background Rural residents' participation in medical insurance has a significant relationship to the affordability of their medical care. This study aims to investigate the willingness of rural residents to participate in basic medical insurance for urban and rural residents and its determinants so as to enhance their willingness to participate in medical insurance. Methods Data were obtained from 1,077 validated questionnaires from rural residents. Chi-square test and multiple logistic regression analysis were adopted to analyze determinants of rural residents' willingness to participate in basic medical insurance for urban and rural residents. Results 94.3% of respondents were willing to participate in basic medical insurance for urban and rural residents and this was associated with the familiarity with the medical insurance policies [OR = 2.136, 95% CI (1.143, 3.989)], the reasonability of medical insurance premiums [OR = 2.326, 95% CI (0.998, 5.418)], the normality of doctors' treatment behavior [OR = 3.245, 95% CI (1.339, 7.867)] and the medical insurance's effectiveness in reducing the economic burden of disease [OR = 5.630, 95% CI (2.861, 11.079)]. Conclusion Even though most respondents were willing to participate in basic medical insurance for urban and rural residents, some aspects need to be improved. The focus should be on promoting and regulating the behavior of medical staff. Financing policies and reimbursement of treatment costs need to be more scientifically developed. A comprehensive basic healthcare system needs to be optimized around the core function of “hedging financial risks”.